INSTRUCTIONAL COHERENCE, SUBNATIONAL GOVERNANCE, AND ECONOMIC COMPETITIVENESS: A VIETNAM-INDONESIA COMPARISON - Ahmad Haibat Kannaby (JF Publisher, 2025)
This study examines how education systems and governance structures interact to produce differential outcomes in human capital development and macroeconomic performance through a comparative analysis of Indonesia and Vietnam from 2013 to 2025. Employing a qualitative comparative case study approach with systematic document analysis, the research synthesizes international indicators (PISA 2022, Human Capital Index 2020, Worldwide Governance Indicators 2023, and FDI and GDP growth data for 2024), national reform policy documents (Indonesia's Merdeka Belajar and Vietnam's Resolution 29), and thematic reports from international institutions. Findings reveal that Vietnam demonstrates superior learning outcomes (PISA scores 103 points higher in mathematics, LAYS 10.7 vs. 7.8 years) and stronger economic performance (7.09% GDP growth, 4.23% FDI/GDP) compared to Indonesia (5.03% GDP growth, 1.73% FDI/GDP). While Indonesia records higher aggregate government effectiveness scores (0.58 vs. 0.13), Vietnam's instructional coherence and Provincial Competitiveness Index create more effective frontline service delivery and investment attraction mechanisms. The study documents specific policy configurations through which Vietnam achieved tighter coupling between education reform, subnational governance competition, and industrial cluster development. These findings contradict conventional assumptions that aggregate governance indicators predict operational-level service quality, revealing instead that instructional system coherence combined with competitive subnational accountability mechanisms may prove more decisive for attracting skill-intensive foreign investment. The research contributes to education-economy linkage literature by systematically connecting classroom-level instructional characteristics with subnational governance mechanisms and macroeconomic outcomes, offering evidence-based policy recommendations for emerging economies seeking to enhance educational effectiveness and investment competitiveness.